Effects of resistance and strength training on serum phosphorus levels in male footballers: implications for physical educators and sports trainers - Ghulam Mustafa; Wasim Khan; Tasleem Arif; Humaira Latif (IP Iermakov S.S., 2024)
Background and Study Aim. Sports performance and overall health of athletes are highly dependent on various physiological markers. Among these, blood biochemistry is of great importance and should be carefully considered in athletes' training regimens. However, the effect of strength and resistance training on serum phosphorus levels still requires further clarification and more effective solutions. The aim of this study was to determine the effect of strength and resistance training on serum phosphorus levels in elite male soccer players. Material and Methods. A sample of 90 volunteers was recruited from football athletes in the Peshawar division. Thirty participants were selected from each of the under-16, under-19, and under-23 age groups. They were divided into three groups: the Resistance Training Group (RTG), the Strength Training Group (STG), and the Control Group (CG). Each group consisted of 30 participants, with 10 from each age category. Phosphorus levels and anthropometric measurements (height, weight, BMI, waist circumference, hip circumference, and waist-to-hip ratio (WHR)) were assessed before and after a 12-week strength and resistance training intervention. Analysis of Variance (ANOVA) and paired sample t-tests were used to evaluate changes over time. Results. Significant improvements were observed in serum phosphorus levels in the Resistance Training Group (4.77±0.258 vs. 3.66±0.207, P<0.001) and in the Strength Training Group (4.31±0.304 vs. 3.66±0.209, P<0.001). A 12-week regimen of strength and resistance training significantly improved serum phosphorus levels among the participants. Analysis of variance indicated that both strength and resistance training significantly affected serum phosphorus levels after 12 weeks of intervention. Tukey's HSD test revealed that the effects of resistance training were more pronounced than those of strength training. Conclusions. This study highlights the importance of incorporating both strength and resistance training in athletic programs. These training approaches are crucial for optimizing physical health and performance. The findings underscore the need for educators and trainers to adapt and refine their methods to maximize the benefits of these interventions. By doing so, they can enhance the effectiveness of training regimens and contribute to the overall well-being of athletes.